The biofilm life cycle: expanding the conceptual model of biofilm formation - Sauer, Karin; Stoodley, Paul; Goeres, Darla M; Hall-Stoodley, Luanne; Burmølle, Mette; Stewart, Philip S; Bjarnsholt, Thomas (Nature reviews. Microbiology, 2022)
Bacterial biofilms are often defined as communities of surface-attached bacteria and are typically depicted with a classic mushroom-shaped structure characteristic of Pseudomonas aeruginosa. However, it has become evident that this is not how all biofilms develop, especially in vivo, in clinical and industrial settings, and in the environment, where biofilms often are observed as non-surface-attached aggregates. In this Review, we describe the origin of the current five-step biofilm development model and why it fails to capture many aspects of bacterial biofilm physiology. We aim to present a simplistic developmental model for biofilm formation that is flexible enough to include all the diverse scenarios and microenvironments where biofilms are formed. With this new expanded, inclusive model, we hereby introduce a common platform for developing an understanding of biofilms and anti-biofilm strategies that can be tailored to the microenvironment under investigation.